Imprisonment and keeping of birds in Islamic jurisprudence: A Comparative Study - Hussain Rasheed Ali (Zanco Journal of Humanity Sciences)
This research deals with an important and contemporary topic, which is “trapping birds”, and I see that some people - and it is increasing day by day - have tended towards the acquisition and confinement of birds for a reason or a motive, and their purpose - with its slanderers and its ramifications - and its utterances. And they forgot or forgot that this poor and weak bird feels as we do, and suffers as we do, and it has a sexual instinct like humans and other animals. The researcher presented the definition and concept of “imprisonment”, “acquisition” and “bird” for linguists, and then I followed it with an idiomatic definition of it, and I formulated it with my own expression, after I did not find it in the mothers of the linguist, and I learned the knowledge of the linguists. And I was exposed to the views of the jurists of the eight schools of jurisprudence, which are (Hanafi, Maliki, Shafi’i, Hanbali, Zaydi, Imami, Dhahiri, and Ibadi) - what we found a way to do so - on the ruling of “the question of which we did not discuss and discuss the other four.” , until I reached the conclusion that the prohibition against trapping birds is most appropriate to the tolerant spirit of Islamic law, which is based on not harming others, even if it is a small bird.Finally, we concluded the research with a conclusion showing the most important findings of the researcher.